Studi Komparatif antara Metode Cost Plus Pricing dan Target Costing dalam Penetapan Harga Jual Produk - Pantja Adiguna Muharam; Ronaldo Dwi Chandra Situmorang; Irma Sesiliya; Bunga Larasati; Husni Mubarok (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Pricing is an important component of marketing strategy and is essential for business sustainability. Cost Plus Pricing and Target Costing are the two most common techniques for determining selling prices. The purpose of this study is to compare the effectiveness of the two methods in determining the selling price of goods, especially considering the aspects of cost through documentation, interviews, and financial statement analysis. The results of the study indicate that Target Costing focuses on cost efficiency to achieve the desired market price, while the Cost Plus Pricing method tends to produce higher selling prices but is less competitive in the market. The results of the study indicate that the pricing method must be adjusted to the characteristics of the.